2016
DOI: 10.1161/atvbaha.116.307839
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin, a Key Mediator Expressed by Senescent Pulmonary Vascular Cells in Pulmonary Hypertension

Abstract: Objective-Senescent pulmonary artery smooth muscle cells (PA-SMCs) may contribute to the pathogenesis of pulmonary hypertension by producing secreted factors. The aim of this study was to explore the role in pulmonary hypertension of extracellular matrix proteins released by senescent PA-SMCs. Approach and Results-Polymerase chain reaction array analysis of human PA-SMCs undergoing replicative senescence revealed osteopontin upregulation, which mediated the stimulatory effect of senescent PA-SMC media and matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 24 publications
(36 reference statements)
5
59
0
Order By: Relevance
“…4 and 5, OPN levels were elevated in proliferating PASMCs as compared with quiescent PASMCs, and OPN promoted PASMC proliferation and migration in dose-and time-dependent manners, whereas antagonizing OPN with neutralizing antibody (LM609) or selective RGD peptide antagonist (XJ735) significantly inhibited and even abolished PASMC proliferation and migration, indicating the reciprocal cause-effect relationship between OPN increase in hypertensive lungs and the advancement of PAH induced by systemicto-pulmonary shunts. This is consistent with a recent study by Saker et al (5), which also confirmed that PASMC-derived OPN stimulates growth and migration of PASMCs. Furthermore, studies have also confirmed that Akt and ERK1/2 signaling pathways were involved in the proliferation and migration of systemic VSMCs and pulmonary adventitial fibroblasts (6,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…4 and 5, OPN levels were elevated in proliferating PASMCs as compared with quiescent PASMCs, and OPN promoted PASMC proliferation and migration in dose-and time-dependent manners, whereas antagonizing OPN with neutralizing antibody (LM609) or selective RGD peptide antagonist (XJ735) significantly inhibited and even abolished PASMC proliferation and migration, indicating the reciprocal cause-effect relationship between OPN increase in hypertensive lungs and the advancement of PAH induced by systemicto-pulmonary shunts. This is consistent with a recent study by Saker et al (5), which also confirmed that PASMC-derived OPN stimulates growth and migration of PASMCs. Furthermore, studies have also confirmed that Akt and ERK1/2 signaling pathways were involved in the proliferation and migration of systemic VSMCs and pulmonary adventitial fibroblasts (6,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 94%
“…1 and 2). This is in accordance with a previous report confirming that OPN was up-regulated in lungs from patients with chronic obstructive pulmonary disease or idiopathic PAH (5). Actually, OPN could be induced in response to pressure or volume overload in systemic arteries (26,27); however, little is known about the expression pattern of OPN in lungs of CHD/PAH suffering volume and pressure overload.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, other authors have demonstrated attenuation of PH and pulmonary vascular remodeling in TRPC6 KO mice after 4 weeks of hypoxia (43). Although the exact reason is not clear, differences in age (44, 45), gender (46), strain, and substrain (47, 48) of mice can account for most of the discrepancies.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%